War, Peace and Liberalism: A Quantitative Approach to the Relation between Economic Globalisation and Armed Conflict (2010)
Signi?cant political, economic, social, and environmental changeshave taken place around the world over the last decades. Amongthem, the deepening of the globalization processes since the 1970s,the adoption of democracy by a number of countries after thecollapse of the Soviet Union, and, as Gutiérrez (Chapter 1) stresses,the expansion and strengthening of neoliberalism. A global openingtowards a “great transformation” in Polanyi’s sense is apparent, witheconomic systems in an increasing number of countries undergoingliberal reforms, and a wider opening by countries already showinghigh degrees of liberalization.After the fall of the Berlin Wall, world economies started showingincreasing liberalization trends, democratic political systems becamestrengthened, and a loss of con?dence in the state as a developmentaltool became apparent. Armed con?icts, on the other hand, did notvanish. While some con?icts had ended before the end of the ColdWar, others have emerged after the fall of the Berlin Wall, whileothers still have become protracted and have undergone changesover time.This study looks at the ways in which armed con?icts have beentransformed or affected by globalization. The possibility of “newwars” (in the sense of Kaldor, 1999) is not being considered here.This research suggests that both the introduction of neoliberalreforms and globalization have, in some ways, had an impact onarmed con?icts—those still continuing, those coming to an end, andthose that have emerged in the midst of these processes.